Enhanced Attraction of Arthropod Vectors to Infected Vertebrates: A Review of Empirical Evidence - Cozzarolo, Camille-Sophie; Glaizot, Olivier; Christe, Philippe; Pigeault, Romain (Frontiers in Ecology and Evolution, 2020)
A large diversity of parasites manipulates their hosts in various ways to complete their own life cycle. Enhancing the attractiveness of their host to vectors has been suggested as a strategy allowing vector-borne parasites to increase their transmission. Indeed, a higher attraction of hematophagous, arthropod vectors to infected vertebrates compared to uninfected individuals has been found in many systems (e.g., Trypanosoma-tsetse flies, Leishmania-sand flies, Borrelia-ticks) but was most often verified in the Plasmodium-mosquitoes model. However, a number of studies found no difference in attractiveness, or a higher attractiveness of uninfected hosts. In this review, we present studies reporting a comparison of the attractiveness and/or the biting rate of infected and uninfected vertebrates. We then discuss several biological factors and experimental design aspects that can explain discrepancies between studies. Finally, we stress the importance of investigating the mechanisms of parasite-induced increased attractiveness of infected hosts to conclude that such observations are cases of adaptive manipulation.